Nesting Biology of Podium angustifrons Kohl (Hymenoptera, Sphecidae) in an Araucaria Forest Fragment - Buschini,MLT. (2014)
Podium angustifrons Kohl 1902 is a species of solitary wasp which nests in pre-existing cavities, with neotropical distribution in Argentina, Bolivia, Brazil, Colombia, Guyana and French Guyana. The aim of this study was to investigate the nesting biology of P. angustifrons, discussing aspects of their life history. To capture its nests, wooden trap-nests were installed in the Parque Municipal das Araucárias, Guarapuava (PR), Brazil, from January 2003 to April 2009. A total of 29 nests were collected, all during the warmer months. These showed no vestibular and intercalary cells, and their closures were made up of chewed plants and mud mixed with organic materials and resin-coated surfaces, sometimes showing a layer of lichens. The cells were provisioned with various wild species of cockroaches (Chorisoneura sp, Riata sp and Helgaia sp) in the nymph stage and/or adults. The sex ratio was 4.6 females per male, significantly higher that the expected 1:1. Most pre-pupae entered diapause in winter with development time ranging from 187 to 283 days for females and 180 to 283 days for males. Deaths occurred in 41.66% of cells provisioned, 33.33% were attributed to faulty development and 8.33% to Chrysididae.